Malassezia pachydermatis keratomycosis in a dog - Ledbetter, Eric C. (Med Mycol Case Rep, 2016)
A 13-year-old female Lhasa Apso was presented for blepharospasm and conjunctival hyperemia of the right eye. Ophthalmic examination revealed an anterior stromal ulcer associated with a raised yellow corneal plaque. In vivo confocal microscopy and cytology of the cornea identified neutrophilic inflammation and yeast cells. Malassezia pachydermatis was isolated from a corneal scraping. Treatment with topical voriconazole ophthalmic solution resolved the keratitis.